Optical solitons to the (1+2)-dimensional Chiral non-linear Schrodinger equation - Ozisik, Muslum; Bayram, Mustafa; Secer, Aydin; Cinar, Melih; Yusuf, Abdullahi; Sulaiman, Tukur Abdulkadir (SPRINGER, 2022)
In this paper, we have successfully extracted many analytic solutions for the (1+2)-dimensional Chiral non-linear Schrodinger equation (NLSE) by the enhanced modified extended tanh expansion method (eMETEM). The considered method is a recently enhanced version of the classical modified extended tanh expansion method. So, we have successfully extracted the abundant solutions of the (1+2)-dimensional Chiral NLSE. Using a computer algebra system program, we have verified that all derived solutions satisfy the Chiral NLSE. The plots of some solutions are demonstrated to explain the dynamics of the solutions. It is expected that the results of the paper might be helpful for future works in traveling wave theory.
Keywords: Chiral nonlinear Schrodinger equation; Soliton solutions; Enhanced modified extended tanh expansion method; COMPLEX WAVE SOLUTIONS; BRIGHT; DARK; Engineering; Physics; Optics